NATION BRANDING THROUGH KNB SCHOLARSHIP AS SOFT POWER DIPLOMACY - Farida Ayu Brilyanti (Dinasti Publisher, 2021)
This study aims to understand how the Developing Countries Partnership (KNB) Scholarship can be used as soft power and improve nation branding that resulted by internationalization of higher education. Using a descriptive approach and utilizing primary and secondary information and data, this research was also enriched by interviews with KNB Scholarship students. The result of this research is that the KNB Scholarship can spread positive views about Indonesia, relations development between countries, and the Indonesian economy promotion by foreign students in their countries. In addition, there are several issues that need to be addressed jointly by cross-stakeholders so that the KNB Scholarship can provide optimal benefits for students, Indonesia’s universities, students' origin countries, and especially for Indonesia.